2012
DOI: 10.1016/j.virol.2012.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a single-stranded DNA virus associated with citrus chlorotic dwarf disease, a new member in the family Geminiviridae

Abstract: In the attempt to identify the causal agent of Citrus chlorotic dwarf disease (CCDD), a virus-like disorder of citrus, the small RNA fraction and total DNA from symptomatic citrus plants were subjected to high-throughput sequencing. DNA fragments deriving from an apparently new geminivirus-like agent were found and assembled by NGS to re-construct the entire viral genome. The newly identified virus has a circular single-stranded DNA genome comprising five open reading frames (ORFs) with sequence homologies wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(77 citation statements)
references
References 36 publications
2
73
0
Order By: Relevance
“…Sequencing of eleven independent clones identified very low nucleotide variability in the circular DNA, substantially consisting of silent mutations in the prevailing variants. Searches in databases for similar sequences and comparisons with other viruses (Tables 1 and S4) were consistent with the possibility that such a circular DNA molecule was the genomic component of a geminivirus related to CCDaV, a divergent geminivirus recently identified in citrus (Loconsole et al, 2012).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Sequencing of eleven independent clones identified very low nucleotide variability in the circular DNA, substantially consisting of silent mutations in the prevailing variants. Searches in databases for similar sequences and comparisons with other viruses (Tables 1 and S4) were consistent with the possibility that such a circular DNA molecule was the genomic component of a geminivirus related to CCDaV, a divergent geminivirus recently identified in citrus (Loconsole et al, 2012).…”
Section: Discussionsupporting
confidence: 72%
“…In the last few years, identification of divergent geminiviruses infecting citrus, grapevine and Jatropha multifida (Al Rwahnih et al, 2013;Krenz et al, 2012;Loconsole et al, 2012;Polston et al, 2014;Poojari et al, 2013) has shown that the host range of geminiviruses is not limited to herbaceous plants. In this study we report the identification and characterization of a novel geminivirus infecting mulberry trees, as an addition to the list of woody plants infected by geminiviruses in nature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1): 1) Becurtovirus: Including the species Beet curly top Iran virus and Spinach curly top Arizona virus (Table 1) [14,18,19,33,39] 2) Eragrovirus: Including the species Eragrostis curvula streak virus (Table 2) [35] 3) Turncurtovirus: Including the species Turnip curly top virus (Table 3) [5,29,30] We additionally acknowledge the need for further new genera to accommodate three other highly divergent groups of geminiviruses that have recently been found infecting grapevines in the USA [22,28] and citrus plants in Turkey [23], as well as two closely related viruses (*72 % genomewide pairwise sequence identity) infecting Euphorbia caputmedusae in South Africa [4] and French beans in India.…”
Section: Introductionmentioning
confidence: 99%